Childhood Arthritis and Rheumatology Research Alliance Consensus Treatment Plans for Juvenile Idiopathic Arthritis–Associated and Idiopathic Chronic Anterior Uveitis. Issue 4 (28th March 2019) - Angeles‐Han, Sheila T.; Lo, Mindy S.; Henderson, Lauren A.; Lerman, Melissa A.; Abramson, Leslie; Cooper, Ashley M.; Parsa, Miriam F.; Zemel, Lawrence S.; Ronis, Tova; Beukelman, Timothy; Cox, Erika; Sen, H. Nida; et al.
Abstract : Objective: Systemic immunosuppressive treatment of pediatric chronic anterior uveitis (CAU), both juvenile idiopathic arthritis–associated and idiopathic anterior uveitis, varies, making it difficult to identify best treatments. The Childhood Arthritis and Rheumatology Research Alliance (CARRA) developed consensus treatment plans (CTPs) for CAU for the purpose of reducing practice variability and allowing future comparison of treatments using comparative effectiveness analysis techniques. Methods: A core group of pediatric rheumatologists, ophthalmologists with uveitis expertise, and a lay advisor comprised the CARRA uveitis workgroup that performed a literature review on pharmacologic treatments, held teleconferences, and developed a case‐based survey administered to the CARRA membership to delineate treatment practices. We held 3 face‐to‐face consensus meetings using nominal group technique to develop CTPs. Results: The survey identified areas of treatment practice variability. We developed 2 CTPs for the treatment of CAU, case definitions, and monitoring parameters. The first CTP is directed at children who are naive to steroid‐sparing medication, and the second at children initiating biologic therapy, with options for methotrexate, adalimumab, and infliximab. We defined a core data set and outcome measures, with data collection at 3 and 6 months after therapy initiation. The CARRA membership voted to accept the CTPs with a >95% approval (n = 233). Conclusion: Using consensus methodology, 2 standardized CTPs were developed for systemic immunosuppressive treatment of CAU. These CTPs are not meant as treatment guidelines, but are designed for further pragmatic research within the CARRA research network. Use of these CTPs in a prospective comparison effectiveness study should improve outcomes by identifying best practice options.